EARLY PROBIOTICS IN PREVENTING VENTILATOR-ASSOCIATED PNEUMONIA AFTER MULTIPLE TRAUMA - HABIB, TAMER; KASSEM, AMIRA B; AHMED, ISLAM (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Using probiotics in preventing ventilator-associated pneumonia (VAP) remain controversial due to different intensive care unit (ICU) populations included in such studies. The aim of this study is to evaluate the role of probiotics in prophylaxis of VAP after multiple trauma. Methods: Sixty-five adult multiple trauma patients on mechanical ventilator (expected ≥48 h) after admission to the Critical Care Medicine Department, Alexandria Main University Hospital from June to November 2018. Patients were randomly assigned using computer sheet into two groups; probiotics group (32 patients received one Lacteol Forte® sachet through orogastric/nasogastric tube 3 times daily during their ICU stay) and control group (33 patients received similar regimen of placebo sachets). All patients were followed up and subjected to all possible strategies of the diagnosis of microbiologically confirmed VAP. Results: Sixty-five patients were enrolled with a mean of age (39.48±7.692) years, 80% of them were male. Regarding the incidence of VAP, it was 18.46% of all patients without statistically significant difference between probiotics group (15.63%) and control group (21.21%) (p=0.751). Conclusion: Routine use of early probiotics in mechanically ventilated multiple trauma patients was not associated with lower incidence of VAP, duration of MV, or ICU mortality.